Influence of Team Rating on Running Performance in Elite Gaelic Football. Issue 9 (September 2018) - Mangan, Shane; Malone, Shane; Ryan, Martin; Mc Gahan, Jason; Warne, Joe; Martin, Denise; O'Neill, Cian; Burns, Con; Collins, Kieran
Abstract : Abstract: Mangan, S, Malone, S, Ryan, M, Mc Gahan, J, Warne, J, Martin, D, O'Neill, C, Burns, C, and Collins, K. Influence of team rating on running performance in elite Gaelic football. J Strength Cond Res 32(9): 2584–2591, 2017—It is currently unknown how team rating influences running performance in Gaelic football. Global positioning system technologies were used to quantify match-running performance within 5 elite Gaelic football teams over a period of 5 years (2012–2016). In total 780 player data sets were collected over 95 matches. Running performance variables included total distance, high-speed distance (≥17 km·h −1 ), and the percentage of high-speed distance. Team ratings were determined objectively using the Elo rating system for Gaelic football. Reference team rating had trivial effects on total distance ( p = 0.011, partial η 2 = 0.008) and high-speed distance ( p = 0.011, partial η 2 = 0.008). Opposition team rating had small effects on total distance ( p = 0.005, partial η 2 = 0.016) and high-speed distance ( p = 0.001, partial η 2 = 0.020). Top-tier teams cover greater total distances and high-speed distance than lower tier teams. Players cover considerably less total distance and high-speed distance against tier-3 and tier-4 teams. Tier-1 players ran a significantly higher percentage of distance at high speed than players who played for tier-2 teams ( p = 0.020). The competitive advantage of top-tier Gaelic football teams is closely linked with their ability to demonstrate a higher physical intensity than lower tier teams.